Genetic Correlation Between Fe and Zn Biofortification and Yield Components in a Common Bean (Phaseolus vulgaris L.) - Diaz, Santiago; Polania, Jose; Ariza-Suarez, Daniel; Cajiao, Cesar; Grajales, Miguel; Raatz, Bodo; Beebe, Stephen E. (Frontiers in Plant Science, 2022)
Common bean (Phaseolus vulgaris L.) is the most important legume for direct human consumption worldwide. It is a rich and relatively inexpensive source of proteins and micronutrients, especially iron and zinc. Bean is a target for biofortification to develop new cultivars with high Fe/Zn levels that help to ameliorate malnutrition mainly in developing countries. A strong negative phenotypic correlation between Fe/Zn concentration and yield is usually reported, posing a significant challenge for breeders. The objective of this study was to investigate the genetic relationship between Fe/Zn accumulation and yield components in common bean. We used QTL mapping and GWAS analysis in three bi-parental populations that included biofortified parents, identifying genomic regions associated with yield and micromineral accumulation. Significant negative correlations were observed between agronomic traits (pod harvest index, PHI; pod number, PdN; seed number, SdN; 100 seed weight, 100SdW; and seed per pod, Sd/Pd) and micronutrient concentration traits (SdFe and SdZn), especially between PHI and SdFe and SdZn. PHI presented a higher correlation with SdN than PdN. 79 QTL were identified for the three populations: 14 for SdFe, 12 for SdZn, 13 for PHI, 11 for SdN, 14 for PdN, 6 for 100SdW, and 9 for Sd/Pd. Twenty-three hotspot regions were identified in which several QTL were co-located, of which 13 hotpots displayed QTL of opposite effect for yield components and Fe/Zn accumulation. In contrast, 8 QTL for SdFe and 6 QTL for SdZn were observed that segregated independently of QTL of yield components. The selection of these QTL will enable enhanced levels of Fe/Zn and will not affect the yield performance of new cultivars focused on biofortification.